Tablet technology to enhance learning motivation for slow learners - Azizzeanna Hassan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
The use of tablet technology has presented a new ambience in a way of learning for children including the learning disabilities and slow learners. The research has been conducted to achieve the objective as to enhance the motivation learning for the slow learners with the use of tablet technology. Apparently, the slow learners have challenges and difficulties to understand complex instructions and taken longer time to catching up in learning. Therefore, the learning for slow learners needs to be different from the traditional learning which practices for the normal main-streams children. The research has foreseen as the learning for slow learners need to include the features such as the animations, audio, graphics and colours. Basically, tablet technology is embedded with these features. Thus, the research has undergone six weeks of observations with a group of ten slow learners in a sub-urban school in Southern Malaysia which consist of the Special Education Integrated Program. During the observations, each slow learner was given the experience of using the tablet technology after the session of traditional learning. The slow learners were required to perform tasks based on the topics learned during the traditional learning. The slow learners were observed by the researcher through the note taking during the traditional learning and with the use of tablet technology sessions. Three of the slow learners' teachers were also involved to observe and evaluate the slow learners especially on the motivation aspects. Interviewed sessions were conducted with the teachers to grasp their perspectives and to support the use of tablet technology as part of the learning tools for the slow learners. The findings of the research has identified as the audio, graphics and the ability to touch and swipe the screen of the tablet device enhanced the motivation of the slow learners in their learning. The research has resulted as the use of tablet technology has increased the attention of the slow learners and they were more focused during their learning. They seemed to enjoy and excited to perform tasks with the tablet technology. The used of the tablet technology has developed the confidence level and the slow learners became fearless with their learning. The research has suggested as the use of tablet technology as the educational and complimentary tool in order to assist the teachers for the slow learners' learning. The research has also followed to recommend several lists of features and guidelines recommendations to assist the apps developer to develop the apps in the tablet technology specifically for the slow learners' users. These contributions and recommendations could benefit the teachers, the apps developer and the policy maker for reducing the digital gap among the slow learners.